Risk factors for hip fracture in black women - Grisso, J.A; Kelsey, J.L; Strom, B.L; O'Brien, L.A; Maislin, G; LaPann, K; Samuelson, L; Hoffman, S (The New England journal of medicine, 1994)
Although more than 1 percent of black women 80 years of age or older have hip fractures each year, little is known about risk factors for hip fracture in these women. We carried out a case-control study involving 144 black women admitted with a first hip fracture to 1 of 30 hospitals in New York and Philadelphia. The controls were 218 black women living in the community who were matched to the case patients according to age and ZIP Code or telephone exchange and 181 hospitalized black women matched according to age and hospital. Information was obtained through personal interviews and was studied by multivariable logistic-regression analysis. When the case patients were compared with the control subjects from the community, the women in the lowest quintile for body-mass index had a markedly increased risk of hip fracture as compared with the women in the highest quintile (odds ratio, 13.5; 95 percent confidence interval, 4.2 to 43.3). Postmenopausal estrogen therapy for one year or more was protective for women under 75 years of age (odds ratio, 0.1; 95 percent confidence interval, 0.1 to 0.5). Factors associated with an increased risk of hip fracture included a history of stroke (odds ratio, 13.1; 95 percent confidence interval, 1.2 to 8.1), use of aids in walking (odds ratio, 5.6; 95 percent confidence interval, 2.7 to 11.5). and consumption of seven or more alcoholic drinks per week (odds ratio, 4.6; 95 percent confidence interval, 1.5 to 14.1). The results were similar when the case patients were compared with the hospitalized control subjects. Among black women thinness, previous stroke, use of aids in walking, and alcohol consumption are associated with an increased risk of hip fracture Postmenopausal estrogen therapy protects against hip fracture in women under 75 years of age